Companion animal adoption and relinquishment during the COVID-19 pandemic: Peri-pandemic pets at greatest risk of relinquishment - Carroll, Grace A.; Torjussen, Alice; Reeve, Catherine (Frontiers in Veterinary Science, 2022)
The COVID-19 pandemic has created a situation globally where companion animals may be at increased risk of relinquishment and abandonment due to multiple interrelated factors. The aims of this study were to establish the prevalence of self-reported adoption and relinquishment of cats and dogs during the pandemic, and to identify characteristics associated with relinquishment. N = 3945 responses were available for analysis. Three groups of participants were identified; Those that never considered relinquishment (NCR), those that have considered relinquishment (CR) and those that have already relinquished a cat or dog (R). Two follow-up surveys were sent to CR and R participants. Considering data from the three surveys, 4.06% of participants considered giving up their pet, 0.74% relinquished their pet, and 0.2% considered and then later give up their pet. Compared to pets given as a gift, there was a 38.7% decreased likelihood of relinquishment in pets sourced from shelter (P < 0.001), 31.2% decrease in those sourced from a breeder, and a 24.4% decrease in those acquired directly from someone that needed to find a new home for their cat or dog. Compared to owners who acquired their pet > 6 months before COVID-19 was declared a pandemic, those acquired < 6 months before COVID-19 was declared a pandemic were three times more likely to be considered for, or be, given up (P < 0.001) and those acquired after COVID-19 was declared a pandemic were two times more likely to be considered for, or be, given up (P < 0.001). There was a trend for greater likelihood of CR or R of pets acquired online (P = 0.074). Of those that had already given up their pet, 14.3 relinquished to a shelter, 66.7% gave their pet to a new owner and 19% obtained temporary care from someone else. A total of 65.0% of CR participants were male, increasing to 72.2% of R participants. Financial constraints were the most mentioned reason for both giving up a pet and considering giving up a pet, followed by health concerns specific to COVID-19, and behavioural problems.